An Exploration of Humanistic Methodologies of Language Teaching: The Silent Way, Community Language Learning, Suggestopedia, Psychodrama - Heah, Lee Hsia Carmel (Journal of Modern Languages, 2017)
This study seeks to explore four unconventional methods of teaching languages: the silent way, community language learning (CLL), suggestopedia, and psychodrama or to give it its French name, 'psychodramaturgie linguistics’. These methods are often indiscriminately lumped together as 'fringe methodologies' and conveniently dismissed as 'gimmicky', ‘fads'. 'creazes', their practitioners being referred to as being on the 'lunatic fringe', which are quite different from each other, both in conception and in realisation. The paper, first, considers identifying the basic features of the 'humanistic' movement with which these methodologies are associated. Next, the theory behind each methodology and the implementation of it in the classroom is outlined, followed by a discussion of how theory and practice relate to each other and to humanistic language teaching as a whole. Finally, the differences between these methodologies in their interpretation of humanistic principles is outlined.